SISTEM INFORMASI PEMESANAN ALAT PRAKTEK KEBIDANAN BERBASIS WEB ORDERING TOOL MIDWIFERY PRACTICE INFORMATION SYSTEM WEB BASED (Information Technology and Telematics, 2015)
Abstrak – Midwifery DIII laboratory is one of the courses UNIMUS health (University of Muhammadiyah Semarang). One of facilities owned by DIII Midwifery Studies is a laboratory which serves to provide the tools that students need practice in lecturing activities. Before doing the practice lectures, students are required to book a practical tool in advance. The system is currently running is still using the manual method. So often troublesome in the laboratory serve students. With the existence of the problem, then be made to the system This practice tool ordering information. The purpose of this research is to make the information system web-based which can be used by the student in making reservations tool practice online. This system can also be utilized in a laboratory provide information about the availability of a practical tool that can be ordered to students and facilitate laboratory in making statements and reservations returns a practical tool. Making the system uses the PHP programming language and MySQL, the methods used in the development of this system is the method prototyping (Collecting Supplies, Building Prototyping, Evaluation prototyping, Encoding System, System Testing, Evaluation System, Using System). This system design results in the form of system-based booking information online web which can be used by students and laboratory Keywods :lab, booking, web-based information system